Central Bank Green Interventions and Financial Stability : An Analysis of Bank Indonesia’s Role in Supporting The Low - Carbon Transition - Farida Ariani; Rusiadi; Lia Nazlia Nasution (Cattleya Darmaya Fortuna, 2026)
Purpose: Climate change has emerged as a systemic source of macroeconomic and financial instability, influencing monetary transmission, credit risks, asset pricing, and capital flows. This study aims to empirically assess how green central bank interventions strengthen Indonesia’s financial stability during the transition toward a low-carbon economy. The analysis focuses on the dynamic impact of the Green Policy Index (GPI)—a composite indicator capturing green communication, collateral frameworks, and liquidity facilities—on the Financial Stability Index (FSI). Methods: Using quarterly data from 2010Q1 to 2025Q2, this study employs a Structural Vector Autoregression (SVAR) model to identify structural shocks and disentangle the causal interactions among GPI, FSI, inflation, policy rates, exchange rates, and global energy prices. Identification relies on short-run restrictions consistent with green monetary policy theory, while impulse response functions (IRF) and forecast error variance decomposition (FEVD) are used to measure the magnitude and persistence of policy effects.Results: The IRF results show that a positive shock to GPI significantly enhances financial stability within 4–6 quarters, with the peak response reaching approximately 0.35 index points. Green interventions stabilize markets through credit, liquidity, and confidence channels while supporting temporary appreciation in the exchange rate. FEVD results indicate that GPI accounts for roughly 38–40% of the variation in FSI over a 12-quarter horizon, surpassing the influence of policy rates, inflation, exchange rates, and global energy shocks.Implications: The findings highlight the strategic role of green central bank interventions as an integral component of macro-financial stability. The study suggests strengthening Indonesia’s green policy mix, integrating climate-based stress testing, and enhancing coordination among monetary, fiscal, and market authorities to ensure a credible, consistent, and effective transition to a low-carbon economy